Efecto del tiempo de envejecimiento en el tratamiento térmico t6 de la aleación zinc - aluminio con 27% de aluminio sobre la dureza, resistencia a la tracción y ductilidad - Naves Ruiz, Francisco Javier (2016)
In the present research experimentally studies the effect of aging time T6 heat treatment (solution and aging) of the zinc alloy - 27 % aluminum. For this purpose the zinc alloy was produced - aluminum with a process of adjusting amounts of pure metals , bars 16 mm diameter x 200 mm casting length was melted in the mold of dry sand , they were machined according to ASTM E- standard 140 for hardness testing and tensile testing according to ASTM E -8. The solution heat treatment was performed at 360 ° C for 1 hour with water quenching and then aging treatment was conducted at 180 ° C for 0.5, 1 , 2, 3 , 4, 5 and 6 hours. It was observed that this alloy has high flowability and is heat treated (T6) because the mechanical properties of hardness, strength and ductility are improved. It also states that the aging time, in the heat treatment T6, suitable for obtaining the best mechanical properties under study is 2 hours. And as the tensile strength and the hardness increase, decreases the percentage of elongation (ductility) due to precipitation of the gamma phase (  ). It is concluded that the aging time T6 heat treatment significantly affect the tensile strength, toughness and ductility in the zinc alloy - aluminum 27% according to the statistical analysis with 95 % confidence.